Risk Management Plan of "Remedies" Postpartum Care Center: Framework for Mitigating Challenges and Enhancing Quality - Irhamdani, Irhamdani; Indradewa, Rhian; Kustiawan, Unggul; Pamungkas, Rian Adi (Jurnal Pendidikan Indonesia, 2025)
Risk management is a critical component of business operations, particularly in the healthcare sector, such as in postpartum care centers. This study aims to design a comprehensive risk management plan for Remedies, a postpartum care center in Indonesia, based on the ISO 31000:2018 standard. The proposed framework encompasses the identification, analysis, evaluation, and treatment of both internal and external risks that could impact service quality, reputation, and financial stability. Short-term, medium-term, and long-term objectives are formulated to ensure alignment with the company’s vision of becoming an innovative and inspirational care center. The methodology employed involves risk analysis based on probability and impact, as well as the implementation of mitigation strategies tailored to Remedies' operational context. The findings reveal that the primary risks faced include clinical, reputational, compliance, operational, and financial risks. Risk treatment strategies focus on enhancing service quality, staff training, revenue diversification, and the adoption of innovative technologies. Additionally, communication and consultation with stakeholders are identified as crucial factors in ensuring the effectiveness of risk management. This study provides practical contributions by offering a risk management framework that can be adapted by other healthcare centers. The recommendations emphasize the importance of regular monitoring, continuous evaluation, and adequate budget allocation for risk management implementation. By adopting these measures, Remedies can mitigate operational challenges, improve service quality, and achieve long-term financial stability.